Impact of Thermal Processing Methods on Polyphenols and Antioxidant Activity of Olive Oil Polar Fraction. Issue 6 (13th January 2015) - Goulas, Vlasios; Orphanides, Antia; Pelava, Elias; Gekas, Vassilis
Abstract: Several health claims of olive oil are correlated with phenolic compounds. The objective of this study was to evaluate the effect of different thermal processing methods on phenolic composition and antioxidant properties of heated olive oils. In particular, the phenolic antioxidants of olive oils, which were subjected to frying, baking, boiling and microwave irradiation, were estimated using multi‐spectrophotometric assays approach. Results showed that thermal processing methods affected significantly the phenolic content as well as the antioxidant potency of heated olive oils. The frying and boiling of olive oils caused the highest losses of phenolic compounds that reached up to 75%, whereas a slight decrease in polyphenols was monitored after microwave irradiation. Furthermore, the baked olive oils retained better phenolic antioxidants than olive oils that were subjected to frying and boiling. Overall, our findings suggest baking as the most appropriate thermal method to heat olive oils. Practical Applications: The present work investigated the influence of thermal processing methods on olive oil polyphenols and their antioxidant properties. Results showed that frying and boiling have to be avoided in heating olive oils, while microwave heating did not decrease statistically the amount of phenolic antioxidants. Based on phenolic content and antioxidant potency, baking of olive oil is preferred when heating of olive oil is required. This study recommended good practices for home‐cooking in order to retain phenolic antioxidants through selecting thermal processing method. Taking into consideration that the food industry uses olive oil to replace meat fat or refined vegetable oils, this work is a useful guide to produce healthier and high added‐value food products.